UJI BEBERAPA DOSIS TRICHOKOMPOS TERHADAP PENYAKIT VIRUS KOMPLEKS, PERTUMBUHAN DAN PRODUKSI TANAMAN TOMAT (Lycopersicum esculentum Mill.) - Marsella, Voni; Ali2, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This research aims to study the effect of various Trichocompost doses to control the virus complex disease and to improve the growth and yield of tomato plants. Research has been conducted at the Laboratory of Plant Pathology and Experimental Field Screen House, Faculty of Agriculture, University of Riau for five months from May to September 2016. The research was conducted experimentally, arranged in a completely randomized design (CRD), consisting of 6 treatments (0, 50, 100, 150, 200 and 250 g/plant) and 4 replications. Data were analyzed statistically by analysis of variance and the means of each treatment was compared by using Duncan's New Multiple Range Test (DNMRT) at 5% level. Results indicated that trichocompost with various doses significantly affected on the first disease symptom appearance and the plant height. Application of trichocompost at dose of 100 g/plant give a better ability to inhibit the first disease symptom appearance, increasing the growth and yield of tomato.Keywords: Trichocompost, Trichoderma sp., complex virus, tomato